METALLOTHIONEIN RESPONSE OF ANINIKAD, CANARIUM LABIATUM (RODING, 1798) TO HEAVY METAL CONCENTRATIONS IN BALAMBAN COASTLINE, CEBU - Geolin, Kristyne Rose C; Villegas, Lora Mae G; Alburo, Rosalyn P (Journal of Agriculture and Technology Management; Vol 24 No 1 (2021): Vol 24 No 1 (2021): Journal of Agriculture and Technology Management (JATM) Volume 24 January - June 2021 Issue, 2021)
Heavy metals in the marine environment pose risk to mollusks and cause undesirable effects to the environment. This study is focused on the potential-threat of trace metals to locally available univalve in the coastline of Balamban, Cebu, Philippines. Sediment along with univalve mollusk samples were collected in the sites. The sediment sample was digested and analyzed for metal concentration by Flame Atomic Absorption Spectrophotometer (FAAS). Toxic effects to the univalve Canarium labiatum ( Aninikad ) posed by heavy metals were quantified in the whole tissue of C. labiatum using metallothionein (MT) assay.The study revealed that the accumulation of metals in sediments had a general trend of Zn>Cu>Pb>Cr>Cd with no seasonal variation while mean concentrations of metals in the soft tissues of the mollusk have the general trend of Zn>Cu>Pb>Cd>Cr in both seasons. This shows that C. labiatum accumulates high concentration of metals when there is a higher level of metals in sediments. The results also showed statistically significant correlations between MT, Zn, Cu, Cd and Pb. This means that accumulation of these metals could influence the concentrations of MT in mollusks. Thus, MT can act as an effective biomarker for Cu accumulation in C. labiatum and it could be used as a valuable biomonitor for heavy-metal pollution. A more detailed study is recommended to understand the capacity of this univalve to induced MT as a response to heavy metal